Communication competence model: how to train ability to say what you really mean - Glushanytsia, Nataliia; Tarnavska, Tetyana; Chernukha, Nadiia; Krupnyk, Zoriana; Kostenko, Dmytro (International Journal of Evaluation and Research in Education (IJERE), 2025)
Business is becoming increasingly multinational. Non-native language communication is a background activity for many jobs and a challenge for those whose first language is not English. The problem is that a non-native language activity distracts attention, increases the risk of misunderstanding, and reduces the effectiveness of professional communication. The article aims to present a Foreign Language Communicative Competence model that is a way to solve the problem and enables fluent, errorless communication that supports professional activity. The main question of the research is what learning conditions, methods and strategies, approaches, and technologies provide the development of foreign language communication competence. We used questionnaires, interviews, psychological diagnostic techniques, observations, and a pedagogical experiment in the research. The pedagogical experiments occurred at the National Aviation University in the 2021 to 2022 academic year. Two groups of second-year students majoring in “Aviation Maintenance” were involved. The experiment outcomes show the enhanced level of students’ foreign language communication competence, motivation, and engagement in learning. The developed model contributes to the ability to concentrate on the job and make quick decisions under the influence of psychological factors like time pressure, stress, or noise while speaking a foreign language.